Pensions at Work: Socially Responsible Investment of Union-Based Pension Funds - Hanin, Frédéric (Relations industrielles / Industrial Relations, 2009)
Pensions at Work: Socially Responsible Investment of Union-Based Pension Funds, edited by Jack Quarter, Isla Carmichael and Sherida Ryan, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Fiduciary responsibility; Investment policy; Labor Unions; Pension funds; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z